FMT-PCCT: Hybrid fluorescence molecular tomography - X-ray phase-contrast CT imaging of mouse models - Mohajerani, Pouyan; Hipp, Alexander; Willner, Marian; Marschner, Mathias; Trajkovic-Arsic, Marija; Ma, Xiaopeng; Burton, Neal C.; Klemm, Uwe; Radrich, Karin; Ermolayev, Vladimir; Tzoumas, Stratis; Siveke, Jens T.; et al. (IEEE Transactions on Medical Imaging, 2014)
The implementation of hybrid fluorescence molecular tomography (FMT) and X-ray computed tomography (CT) has been shown to be a necessary development, not only for combining anatomical with functional and molecular contrast, but also for generating optical images of high accuracy. FMT affords highly sensitive 3-D imaging of fluorescence bio-distribution, but in stand-alone form it offers images of low resolution. It was shown that FMT accuracy significantly improves by considering anatomical priors from CT. Conversely, CT generally suffers from low soft tissue contrast. Therefore utilization of CT data as prior information in FMT inversion is challenging when different internal organs are not clearly differentiated. Instead, we combined herein FMT with emerging X-ray phase-contrast CT (PCCT). PCCT relies on phase shift differences in tissue to achieve soft tissue contrast superior to conventional CT. We demonstrate for the first time FMT-PCCT imaging of different animal models, where FMT and PCCT scans were performed in vivo and ex vivo, respectively. The results show that FMT-PCCT expands the potential of FMT in imaging lesions with otherwise low or no CT contrast, while retaining the cost benefits of CT and simplicity of hybrid device realizations. The results point to the most accurate FMT performance to date. © 1982-2012 IEEE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computed tomography (CT); fluorescence imaging; molecular imaging; phase contrast imaging; tomography